Cigarette smoking increases deaths associated with air pollution in Hong Kong. (15th February 2020) - Sun, Shengzhi; Cao, Wangnan; Chan, King-Pan; Ran, Jinjun; Ge, Yang; Zhang, Yunquan; Feng, Yilin; Zeng, Qiang; Lee, Ruby Siu-yin; Wong, Chit-Ming; Tian, Linwei; Lei, Yujie
Abstract: Background: Ambient air pollution and cigarette smoking are two significant risk factors for mortality; however, less is known about their interaction. Objectives: We aimed to examine effect modification of cigarette smoking on the association between short-term exposure to air pollution and mortality in the Chinese Elderly Health Service Cohort in Hong Kong. Methods: We included 16, 290 Chinese elders aged 65 years or older who died between 1 July 1998 and 31 December 2011. Smoking history was collected through face-to-face interviews by registered nurses or doctors using a standardized structured questionnaire when they were recruited into the cohort. We used a time-stratified case-crossover approach to estimate the percent excess risk (ER%) of all-natural mortality per 10 μg/m 3 increase in fine particulate matter (PM2.5 ), respirable particulate matter (PM10 ), and nitrogen dioxide (NO2 ) among current-, ex-, and never-smokers, and to estimate the additional percent excess risk (ΔER%) for current- and ex-smokers relative to never-smokers. We performed secondary analysis to assess whether the estimated additional risks varied by personal characteristics. Results: There were greater ERs % associated with air pollutants among current- and ex-smokers relative to never-smokers. We found ΔER% per 10 μg/m 3 increase in air pollutants was statistically significant for PM2.5 among ex-smokers [2.63% (95% CI: 0.39%, 4.88%) at 1 day prior to death (lag1 )], and PM10 among current-smokers [2.21% (95% CI: 0.08%, 4.33%) at lag1 ] and ex-smokers [1.96% (95% CI: 0.26%, 3.65%) at lag1 ]. The increased risks associated with cigarette smoking were more pronounced among males, overweight or obese elders, elders with three or more comorbidities, or elders received primary or lower education. Conclusion: Ever-smokers were more susceptible to excess mortality risk associated with daily air pollution, especially for males, overweight or obese elders, and those with poor health conditions or received lower educational attainment. Tobacco control can reduce the health burdens attributable to air pollution. Highlights: Ever-smokers are more susceptible to short-term air pollution exposure. The higher risks due to smoking are stronger among males, overweight elders, or elders with worse health. Tobacco control can reduce health burdens attributable to air pollution.